AFFECTIVE BIBLIOTHERAPHY UNTUK MENINGKATKAN SELF ESTEEM PADA ANAK SLOW LEARNER DI SD INKLUSI - Ekowati, Dian (EMPATHY Jurnal Fakultas Psikologi, 2015)
AbstrackSelf-esteem is an important factor affecting the success of a child for a happier life. Have a high self esteem is a difficult thing for a slow learner child in elementary inclusive. This study aims to determine the level of self-esteem slow learner children in elementary inclusion school, and improving their self esteem with affective bibliotherapy techniques.The design of this study using randomized groups pre-test post-test design. This research involves with 9 slow learner children with 4 children as the experimental group and 5 children as a control group. The experimental group was given training bibliotherapy for 10 times.The study have two hypothesis, the first is âAffective bibliotherapy to increase self esteem slow learner children in inclusive elementary schoolâ, and the second hypothesis is âThere is an increase in self esteem between experimental group with the control group after the intervention with the experimental group was affective bibliotherapy.Research results show that affective bibliotherapy is effective for improving slow learner childrens self esteem in primary inclusions with z value = -1,841 with 0.033 significansi level (p <0.05). It is also found that the affective bibliotherapy more effective in improving three aspects of self-esteem is significant, virtue, and competence, but the aspects of power increase is not to high.Key word: self esteem, slow learner, affective bibliotherapy.